A REVIEW OF TEACHING PASSIVE VOICE STRATEGY - Salma Putri Islamy; Nita Kaniadewi (EPIGRAM (e-journal), 2022)
The difficulty of teaching passive voice has caused several researchers to conduct research on applying various strategies or methods to increase students' understanding of passive voice. Some have succeeded in increasing the effectiveness of passive voice learning although there is still a weakness. This is because the effectiveness of passive voice learning is also influenced by various things, including the level of education of the studied population. Specific strategies may be required for each education level. This study is intended to recapitulate research related to passive voice teaching and analyze the advantages and weaknesses of those methods so that teachers can better adapt to their classroom conditions. This research was conducted by reviewing research journals related to passive voice teaching and analyzing the advantages and disadvantages of the used method. The result of this study is a recapitulation of conducted research regarding passive voice learning for the last 5 five years, completing the advantages and disadvantages of each method. So that, later the English teacher can choose which method is the most appropriate for their students. On the other hand, other researchers can also choose which method needs further research.